Examination of the effects of learning capabilities and market orientation of logistics companies on innovation and logistics performance - Adiguzel, Zafer; Cakir, Fatma Sonmez; Zehir, Songul Yesilot; Zehir, Cemal (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeIn today's economic conditions, businesses face great challenges related to competitiveness. The effort to respond flexibly to the changing business environment and customers' demands constantly puts pressure on innovation. For this reason, research purpose to examine the effects of learning capabilities and market orientation in logistics companies during the pandemic.Design/methodology/approachIn this research, a quantitative method was adopted and partial least squares structural equation modeling (PLS-SEM) was applied. The research is based on four variables. A conceptual research model was established through literature review and the model was tested. Within the scope of this research, A sample of 544 participants was taken to construct and test the model, and a 39-statement scale was presented to them. After presenting the reliability and validity values on the model, hypotheses were tested. Analyses were conducted using Smart-PLS 3.3 software.FindingsAs a result of the research conducted in logistics companies, the positive effects of learning orientation on performance outputs and the positive effects of market orientation as both a mediator and an independent variable show that these concepts are important for company management.Research limitations/implicationsConsidering the limitations of the research, it would be wrong to generalize the results of the analysis for different sectors because the data were collected from experts working in logistics companies. Therefore, it is necessary to make evaluations taking into account the limitations of the research. In future studies, it is recommended to make comparisons with research in different sectors, taking into account the limitations, and to enrich the literature with more research in this area.Practical implicationsBecause of the importance of logistics activities seen in all countries with the pandemic period, it can be explained as a result of the analyses that the performance outputs are positively affected by the learning orientation, the companies' adaptation to continuous change and development and their emphasis on market orientation at the same time.Originality/valueThe research is an original study as it analyzes the effects of learning orientations of logistics companies on the problems and opportunities experienced in the supply and distribution channel along with the pandemic process.
Keywords: Learning capabilities; Market orientation; Logistics performance; Innovation performance; ENTREPRENEURIAL ORIENTATION; COMPETITIVE ADVANTAGE; MODERATING ROLE; MANAGEMENT; IMPACT; VARIABLES; Business & Economics